Testing the risk premium and cost-of-carry hypotheses for currency futures contracts - SEQUEIRA, J. M. (Institutional Knowledge at Singapore Management University, 2000)
The Risk Premium and Cost-of-Carry hypotheses regarding the pricing of futures contracts are tested using nested and non-nested procedures. Cointegrating relationships among the Australian dollar spot and futures prices, and US and Australian risk-free rates of interest, suggest an error-correction representation for the Risk Premium model, and two alternative error-correction formulations for the Cost of-Carry hypothesis. Two significant structural breaks in the futures price series permit a testing of appropriate models for the full sample in the presence of these breaks, for the full sample without explicitly modelling the breaks, and for various subsamples created by these structural breaks. Unit root and cointegration tests yield alternative non-nested formulations of the Cost-of-Carry model for three different subsamples, thereby leading to the use of nested and non-nested tests. The outcomes of these tests provide substantial support for the Cost-of-Carry hypothesis in the pricing of Australian dollar futures contracts.